Perlindungan Objek Sipil dalam Konflik Bersenjata Menurut Hukum Humaniter Internasional - Safiun, Safiun; Tahamata, Lucia Charlota Octavina; Daties, Dyah Ridhul Airin (Faculty of Law Universitas Pattimura, 2025)
Armed conflict not only affects the civilians who are the targets of the conflict, but civilian objects are also affected by the conflict. Civilian objects are any object that is not a military object so that it cannot be used as an object of attack by one of the parties to the conflict. The protection of civilian objects is regulated in Article 52 paragraph (1) and Article 57 paragraph (1) of the Additional Protocol to the Geneva Convention 1494. In addition to being regulated in the article, the protection of civilian objects is also regulated by International Humanitarian Law through principles recognized in HHI such as the principle of Proportionality, the principle of Distinction and the principle of military interests. Violation of the protection of civilian objects in armed conflict is a war crime. Basically, the responsibility for war crimes lies with the individual who committed the violation of the laws and customs of war. The accountability process is carried out through a trial at the ICC (International Criminal Court) where war crimes are the jurisdiction of the ICC itself. War crimes can also be held accountable to the state as well as the commander.